Properties of individual YBCO layers in a two-layered design for energy-efficient digital data cables - Yonamine, Anne H. [UNESP]; Dos Santos, Dayse I. [UNESP]; Pan, Alexey V.; Fedoseev, Sergey A.; Oakden, David; Parsons, Bradley; Shcherbakova, Olga V.; Golovchanskiy, Igor A.; Masilamani, Nandhagopal; Webber, Robert J.; Mukhanov, Oleg A. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
We are developing two-layered Yttrium Barium Copper Oxide (YBCO) thin film structures for energy efficient data links for superconducting electronics and present the results of their property measurements. High temperature superconductors (HTS) are advantageous for the implementation of energy-efficient cables interconnecting low temperature superconductor-based circuits and other cryogenic electronics circuits at higher temperature stages. The advantages of the HTS cables come from their low loss and low dispersion properties, allowing ballistic transfer of low power signals with very high bandwidth, low heat conduction and negligible inter-line crosstalk. The microstrip line cable geometry for typical materials is a two-layered film, in which the two superconducting layers are separated by an insulation layer with a minimized permittivity. We have made a proof of concept design of two YBCO films grown by pulsed laser deposition and then assembled into a sandwich with uniform insulating interlayer of tens of micrometers thick. We report on results obtained from such systems assembled in different ways. Structural and electromagnetic properties have been examined on individual films and on the corresponding sandwich composite. © 2013 IEEE.
Keywords: data link; interconnect; low loss; low thermal conductivity; two-layered design; YBCO thin film